Clinical Features and Treatment Responses of Children With Eosinophilic Gastroenteritis - Fu-Mien Tien; Jia-Feng Wu; Yung-Ming Jeng; Hong-Yuan Hsu; Yen-Hsuan Ni; Mei-Hwei Chang; Dong-Tsamn Lin; Huey-Ling Chen (Elsevier, 2011)
Clinical features and treatment responses in pediatric patients with eosinophilic gastroenteritis are rarely reported. This study aimed to evaluate the clinical manifestations and outcome of eosinophilic gastroenteritis in children of Asian background. Methods: Between 1997 and 2009, 14 Taiwanese patients (nine boys and five girls), with median age of 8.3 years (range, 1.4-14.3 years), were diagnosed with eosinophilic gastroenteritis. The diagnosis was confirmed by the presence of gastrointestinal symptoms, peripheral eosinophilia, and a histology-proved biopsy. The clinical data and responses to medical treatment were analyzed. Results: Initial symptoms included abdominal pain (43%), anemia (36%), hypoalbuminemia (14%), recurrent vomiting (7%), bloody stool (7%), and growth failure (7%). Peripheral eosinophilia was present in 10 patients (71.4%) and positive stool occult blood in seven patients (50%). Endoscopic examination revealed ulcer disease in four patients (28.6%). The treatment included steroid alone, montelukast alone, steroid+montelukast, and steroid+montelukast+ketotifen. Among the patients treated with steroid, two (two of nine, 22%) had successfully tapered off steroid without recurring symptoms. Three patients (three of nine, 33%) had relapses after discontinuing steroid, three (three of nine, 33%) still required low-dose steroid, and one lost to follow-up. There was no relapse in the four patients treated with montelukast alone. Conclusions: A high percentage of patients presented with gross or occult gastrointestinal bleeding with or without abdominal pain. Endoscopic biopsy is necessary for diagnosis. Steroid was the mainstay treatment for active diseases; montelukast was also effective for the disease or as a maintenance therapy in this study.